PARTICIPANTS REPRESENTATION IN NEWS ABOUT INDONESIA IN BBC WORLD WEBNEWS*) - Diah Supatmiwati (LPPM Universitas Bumigora Mataram, 2018)
News is a specific text of media discourse that has attracted special interest. This study gains insight into how linguistic choices shape the representation of information in news stories. Because they involve decision by definition, choices have an impact on the news angles and consequentially on the content and the message conveyed in an article. Specific structures, such as passive sentences, are not only determined by simple stylistic preference, but are also the fruit of linguistic choices. The choice of such constructions in place of factually equivalent or similar ones, gives a sentence a particular direction and indicates a linguistic strategy in the (re)presentation of the facts and the speaker’s attitude. A study on an integral aspect of language use such as linguistic choices applied to news stories is of particular interest because of the essential role language plays in media and communication in general. More specifically, the present thesis is situated in the particular context of foreign news reporting, which involves also editorial choices. The main theoretical framework of this study lies on systemic functional linguistics, from which the concept of linguistic choices originates, and discourse analysis, in its particular application to news texts. This study investigates linguistic choices through the systemic functional linguistic analysis of New about Indonesia in BBC International webnews. The selected web news consists in set BBC world news. The news contains an Indonesia News. The general purpose is to observe how Indonesian was portrayed in the BBC International Website or it can be said how Indonesian is portrayed by the world